A Life Test Power Supply Utilizing Thyratron Rectifiers - Lord, H.W. (Proceedings of the Institute of Radio Engineers, 1933)
Thyratron rectifiers for supplying high voltage direct current to radio transmitting tube life test racks are superior to motor-generator sets where quietness, flexibility, low operating cost, and safe operation over long intervals of time are desirable. An installation for supplying typical voltages, in conjunction with usual forms of electric power supplies is described. This consists of two high power rectifiers for 425 and 1000 volts direct current plate supplies and a low power 125-volt direct current rectifier for bias voltage. A control circuit provides complete protection against faults detrimental to tube operating conditions such as low filament voltage, low bias, and resumption of power after failure, insuring a maximum of life testing hours available consistent with safe operation.